Access Control and Security Monitoring in Blockchain-Based Cloud Information Systems: A Systematic Review - Hayati, Euis Neni (International Journal of Research and Applied Technology (INJURATECH), 2025)
The integration of blockchain technology into cloud information systems has emerged as a promising approach to enhance data transparency, trust, and security. However, the transition toward a decentralized and distributed architecture introduces novel challenges, particularly concerning the enforcement of access control and security monitoring mechanisms within cloud environments. This study presents a systematic literature review focusing specifically on the access control models and security monitoring strategies implemented in blockchain-based cloud systems. Based on the analysis of recent peer-reviewed studies filtered through a structured methodology, the findings indicate that smart contract-driven Role-Based Access Control (RBAC), Attribute-Based Access Control (ABAC), and Capability-Based Access Control (CapBAC) are the dominant approaches for autonomous authorization management. In terms of security monitoring, blockchain-enabled audit logs have proven to provide a high degree of traceability and absolute tamper resistance, effectively mitigating malicious insider threats. Despite these significant advantages, this review identifies that scalability issues, high network latency, and computational costs remain critical bottlenecks for industrial-scale adoption. Consequently, this review highlights current research gaps and recommends future research directions, including the implementation of off-chain scaling solutions, Zero-Knowledge Proofs (ZKPs) for enhanced privacy.